EVALUASI AWAL UJI KETURUNAN SENGON (Falcataria molucca) UMUR 8 BULAN DI KABUPATEN KEDIRI JAWA TIMUR - Burhan Ismail; Yayan Hadiyan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Falcataria moluccana seedling seed orchards was established in 2006 located in Kediri East Java in collaboration between the Center for Forest Biotechnology and Tree Improvement Research and Development and Perum Perhutani. 77 open-pollinated families from four seed sources were progeny tested in Pare Kediri, East Java. The trial was arranged in a randomized completely block design, 4 tree line plot and replicated 6 times. At 8 months of age there were significant differences among seed sources for diameter. The survival rate of family varied from 54.2 % to 86.5%. Difference betwen families within seed sours were significant only for diameter growth. Heritability estimanes for diameter were moderate (h2i= 0.16; h2f = 0.42).).Genetic correlation beetwen diameter and height was strong (rg = 0.89) and higher than phenotipic correlatione (rp = 0.86).